Pyrolysis-catalysis for waste polyolefin conversion into low aromatic naphtha. (1st October 2021) - Dai, Leilei; Zhou, Nan; Lv, Yuancai; Cobb, Kirk; Cheng, Yanling; Wang, Yunpu; Liu, Yuhuan; Chen, Paul; Zou, Rongge; Lei, Hanwu; Ruan, Roger
Graphical abstract: Highlights: Pyrolysis coupled with a tandem catalysis process for upcycling waste polyolefinic plastics. Zn/SBA-15 is the most effective cracking catalyst with the minimal aromatic selectivity. High quality naphtha with the C5-C12 paraffin selectivity of 50–71% is produced. The proposed process is applicable to the real-world plastic mixture. Abstract: The global waste plastic crisis, caused by overconsumption of single-use plastics, is threatening ecological systems and public health, worldwide. This study presents a novel catalytic conversion of waste polyolefinic plastics to low aromatic naphtha for new plastic manufacturing by a tandem catalysis process. Zn/SBA-15 was found to be an effective heterogeneous catalyst for cracking high density polyethylene (HDPE) pyrolytic wax into short chain olefins. This catalyst shows a much higher activity than pure catalysts or SBA-15 catalysts that were modified with other metals. This tandem catalysis system was also applicable to catalytic reforming of various waste polyolefins including HDPE, low density polyethylene (LDPE), and polypropylene (PP), producing high quality naphtha with a C5-C12 paraffin selectivity of 50–71 % peak area. Furthermore, the pure and real-world plastic mixture can also be used to produce high quality naphtha, with a C5-C12 paraffin selectivity of 60.39 % peak area and 57.16 % peak area, respectively. This new plastic to low-aromatic naphtha technology highlights the feasibility of upcycling waste plastics into virgin plastic products.